ChemInform Abstract: Chromium(II)‐Catalyzed Amination of N‐Heterocyclic Chlorides with Magnesium Amides. Issue 38 (3rd September 2015) - Steib, Andreas K.; Fernandez, Sarah; Kuzmina, Olesya M.; Corpet, Martin; Gosmini, Corinne; Knochel, Paul
Abstract The ligand‐free chromium dichloride‐catalyzed selective amination of mono‐ and dichlorinated pyridines, quinolines, isoquinolines, and quinoxalines with various amines is reported.